Plasma DNA as a potential biomarker for breast cancer detection - Dewajani Purnomosari; Ulfah Dian Indrayani; . Irianiwati; Dian Caturini Sulistyoningrum (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Breast cancer is a major malignancy among Indonesian women. It is often diagnosed inthe later stages of cancer, which leads to poor prognosis and survival of the patients.This study investigated plasma DNA concentration as a potential biomarker for breastcancer. The benefit of using this detection is the cost-effectiveness and the samples canbe collected from patients using non-invasive methods. Plasma samples were obtainedfrom healthy controls (n=18) and cancer patients (n=22). Each sample was split intotwo equal portions for DNA isolation using two different methods for the NaI methodand a commercially available kit (Qiagen/ QA) method. The DNA concentration wasdetermined by using a GeneQuant spectrophotometer (Pharmacia). The t-test was usedfor statistical analysis, which was performed using the SPSS 17.0 software. Compared tothe commercial method, extraction using NaI yielded higher DNA concentration, both fromsamples of healthy controls and cancer patients (p=0,008 and p=0.000, respectively).Furthermore, regardless of the isolation method used, the plasma DNA concentrationwas higher in healthy controls than in cancer cases (p=0,032 and p=0.005, for NaIand QA methods, respectively). In conclusion, isolation methods significantly affect DNAconcentrations. The plasma DNA concentration of healthy controls is significantly higherthan those of the cancer cases, suggesting that plasma DNA concentration might be apotential biomarker for breast cancer detection with less invasive sampling method thantissue biopsies.